Derivation of a rotation curve model based on time of events theory and its application on samples of several spiral galaxies - Azeez, Jazeel H.; Fadhil, Sadeem Abbas; Zamri Zainal Abidin, (Penerbit Universiti Kebangsaan Malaysia, 2024)
A new model of rotation curves in spiral galaxies is derived and applied to several spiral galaxies. This model is based on a new theory called the ‘time of events’ theory, which was published elsewhere. The theory led to derive a multiscale model that applies to the problem of rotation curves in the galaxies as a non-adiabatic system. The equations of the derived multiscale model will be generalized in the current work to apply to the gases inside the galaxy to reach a general semi-empirical model that relates rotational velocity with the galaxy radius. The derived equation showed an excellent agreement with experimental results for five galaxies. The findings showed that the bulge plays a limited role for the galaxies with large extensions like IC 2574 and NGC 3198, where the dark matter in the halo region controls and determines the shape of the diagram of the rotation curves in these galaxies. Furthermore, in three bared galaxies NGC 1068, NGC 1097, and NGC 6503, the bulge has the most major role in controlling the rotation dynamics in these galaxies.